Rancang Bangun Website SMP Swasta Karya Bhakti Medan - Maulana Firjatullah; Muhammad Risky Akbar; Ahmad Taufik Al Afkari Siahaan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
In today's digital landscape, rapid and accurate access to information has become a fundamental requirement for educational institutions. Previously, SMP Swasta Karya Bhakti Medan relied heavily on conventional methods for disseminating information, such as verbal communication or limited printed media. This situation frequently resulted in delays in delivering news to guardians and limited the promotional reach to the broader community. Addressing these issues, this internship project focuses on the design and development of a school profile website as a solution for information digitalization. The system development process involved several stages, including field data collection, user-friendly interface design, and the coding implementation phase. The website is designed to host essential information, ranging from the institutional profile, vision and mission, and facilities, to student activity documentation. To ensure optimal accessibility, the site is hosted using the Netlify service, allowing for continuous online access. The final outcome of this project is a responsive and easily accessible digital information portal. The presence of this website is expected to enhance the school's image and facilitate parents and prospective students in obtaining valid information regarding SMP Swasta Karya Bhakti Medan without distance or time constraints.